Delving into immune modulation: thymectomy in myasthenia gravis - Nanlong Lin; Zhongshan Yang; Weiqiang Yi; Yanxun Chen; Fancai Lai (Journal of Cardiothoracic Surgery)
Abstract Objective The study aims to investigate the impact of thymectomy (TX) on immune function and cytokines levels in patients with myasthenia gravis (MG). Methods A total of 44 patients with MG were enrolled in the study, divided into two groups based on the treatment they received: the MG-TX group (14 MG patients who underwent thymectomy) and the control group (30 MG patients who received drug treatment alone). Patients were assessed at baseline (0 months), 1 month, 3 months, 6 months, and 12 months post-treatment. The levels of T lymphocytes subtypes (CD3+, CD4+, CD8 + T cells, and the CD4+/CD8 + ratio), immunoglobulins and complements levels (IgG, IgM, IgA, C3 and C4), and cytokines (IL-2, IL-4, IL-6, INF-γ, and TNF-α) were measured and compared between the two groups. Results At baseline, both the MG-TX and control groups exhibited similar levels of immune markers. Following thymectomy, there was a significant decrease in CD3+, CD4+, and CD8 + T cell levels at 1 month, which remained stable throughout the study period. At 12 months, the CD4 + levels in the MG-TX group were significantly lower than in the control group (P < 0.001). Additionally, the CD4/CD8 ratio was significantly lower in the MG-TX group at both 6 months and 12 months (P < 0.01 and P < 0.001, respectively). No significant changes in immunoglobulin and complement levels were observed in either group throughout the study. For cytokines, IL-2, IL-6, INF-γ, and TNF-α levels decreased significantly at 1-month post-treatment (P < 0.001). At 3 months, INF-γ levels in the MG-TX group remained higher than in the control group (P < 0.001), but stabilized by 6 months and 12 months. IL-4 levels significantly increased at 1 month post-treatment (P < 0.001), but at 12 months, the control group had higher IL-4 levels than the MG-TX group (P < 0.05). Conclusion Thymectomy in MG patients results in a long-term decrease in T lymphocyte levels and a shift in the CD4/CD8 ratio. The procedure also induces transient changes in cytokine levels, which stabilize after 3 months. These findings suggest that thymectomy has a lasting impact on cellular immunity and cytokine secretion, with potential implications for immune system function and the risk of infections in MG patients.